Fundamentals of Friction and Wear - Gnecco, Enrico; Meyer, Ernst (NanoScience and Technology, 2007)
In the past twenty years, powerful tools such as atomic force microscopy have made it possible to accurately investigate the phenomena of friction and wear, down to the nanometer scale. Readers of this book will become familiar with the concepts and techniques of nanotribology, explained by an international team of scientists and engineers, actively involved and with long experience in this field. Edited by two pioneers in the field, 'Fundamentals of Frictions and Wear at the Nanoscale' is suitable both as first introduction to this fascinating subject, and also as a reference for researchers wishing to improve their knowledge of nanotribology and to keep up with the latest results in this field.